The use of E-learning platforms by early childhood education diploma (female) students at Damascus (Damascus University Journal of educational and Psychologyical sciences, 2025)
This study aims to explore the extent to which e-learning platforms are used by female diploma students in the field of early childhood education at Damascus University. It sheds light on their views towards these platforms, which shape the extent to which they utilize them in their studies. To achieve this aim, the researcher collected empirical data through two surveys. The first survey consisted of personal data and 15 statements, and the second survey was an opinion survey about e-learning platforms. The surveys covered a sample of 50 students in the second semester of the academic year 2022-2023. The analysis of the data has shown that the use of e-learning platforms is low among these students and that these students had a non-enthusiastic view toward these platforms. Moreover, the analaysis has shown that there exists statistically significant differences between these students concerning the impact of the length of their professional experience on their use of e-learning platforms.
Keywords: E-learning Platforms; Early Childhood; Diploma Students